Kepulauan Aru dan Integrasi Kebangsaan dalam Perspektif Sejarah dan Budaya - Mezak Wakim (Kapata Arkeologi, 2014)
National integration is a central issue in the context of the management of the foremost islands in Indonesia. Aru Islands is one of the areas in Moluccas which became the region’s leading Indonesian island. This paper aims to address issues related to the Aru Islands national integration as one of the leading regions in Indonesia. Discussions focused on the perspective of history and culture as one of the approaches in addressing the issue of national integration. Therefore, use literature to illustrate the historical and cultural Aru Islands. The results of the discussion of an understanding that the similarity of historical and cultural background of the Aru Islands and surrounding areas provide awareness of the importance of national integration in the management of the outer islands in Indonesia.Integrasi kebangsaan merupakan isu sentral dalam konteks pengelolaan pulau terdepan di Indonesia. Kepulauan Aru adalah salah satu wilayah di Maluku yang menjadi kawasan bagi pulau terdepan di Indonesia. Tulisan ini bertujuan untuk menjawab permasalahan terkait isu integrasi kebangsaan bagi Kepulauan Aru sebagai salah satu wilayah terdepan di Indonesia. Pembahasan difokuskan pada perspektif sejarah dan budaya sebagai salah satu pendekatan dalam menjawab isu integrasi kebangsaan. Oleh karena itu, digunakan studi pustaka untuk memberi gambaran historis dan kultural Kepulauan Aru. Hasil pembahasan memberi pemahaman bahwa kesamaan latar belakang historis dan kultural Kepulauan Aru dan sekitarnya memberi kesadaran akan pentingnya integrasi kebangsaan dalam pengelolaan pulau-pulau terdepan di Indonesia.